Does Retrogression Always Account for the Large Volume of Submarine Megaslides? Evidence to the Contrary From the Tampen Slide, Offshore Norway. Issue 2 (23rd February 2021) - Barrett, R. S.; Bellwald, B.; Talling, P. J.; Micallef, A.; Gross, F.; Berndt, C.; Planke, S.; Myklebust, R.; Krastel, S.
Abstract: Submarine landslides can be several orders of magnitude larger than their terrestrial counterparts and can pose significant hazards across entire ocean basins. The landslide failure mechanism strongly controls the associated tsunami hazard. The Tampen Slide offshore Norway is one of the largest landslides on Earth but remains poorly understood due to its subsequent burial beneath up to 450 m of sediments. Here, we use laterally extensive (16, 000 km 2 ), high‐resolution processed 3‐D seismic reflection data to characterize the upper Tampen Slide. We identify longitudinal (downslope, movement‐parallel) chutes and ridges that are up to 40 m high, as well as extensional and compressional (cross‐slope) ridges. This is the first time that longitudinal ridges of such size have been imaged in a deep marine setting. The first phase of the Tampen Slide involved the simultaneous translation of over 720 km 3 of sediments along a single failure plane. This was followed by spreading along the head‐ and sidewall, and the formation of a retrogressive debris flow and slump, the volumes of which are insignificant compared to the first failure. The process responsible for movement of such a large sediment volume along a single glide plane differs significantly from that of other passive margin megaslides, which typically comprise numerous smaller landslides that fail retrogressively along multiple glide planes. The trigger mechanism (e.g., an earthquake), the presence of mechanically strong obstructions (e.g., volcanic structural high), and the number and location of weak layers may be key factors that determine whether megaslides develop along a single plane or retrogressively. Plain Language Summary: Submarine landslides can be significantly larger than those that occur on land and can cause damaging and widespread tsunami. Furthermore, submarine landslides can also damage critical offshore infrastructure, including telecommunication cables that now carry >95% of global data traffic. However, we still lack fundamental understanding about how such landslides fail. This is critical to understand because it determines the magnitude of associated tsunami. Here, we use exceptionally detailed 3‐D seismic data to understand how one of the largest landslides on Earth, the Tampen Slide offshore Norway, failed. We find that the Tampen Slide failed mainly as a single volume along a single failure surface. This differs significantly from how other giant submarine landslides seem to have failed: in multiple phases and involving multiple failure surfaces that migrated upslope. This was thought to be the only way that giant submarine landslides developed, with multiple smaller landslides accounting for the large total volume. Here, we show for the first time that large submarine landslides can also fail along a single surface across an extensive area, possibly favoring generation of particularly large tsunami. Other large submarine landslides may also fail similarly, and this new model should be included in future hazard assessments. Key Points: We use high‐resolution processed 3‐D seismic data to characterize the headwall of the Tampen Slide, one of the largest landslides on Earth The first phase of the Tampen Slide involved the simultaneous translation of more than 720 km 3 of sediments along a single failure plane Our model shows that retrogression (bottom‐up development) may not account for the large volumes of all giant submarine landslides